LEXICALLY-BASED APPROACH IN ELT: A State of the Art - Jupri Jupri; Arif Rahman (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
This paper explores the most recently issues in English language teaching known as lexically-based approach and discusses the current issues and promising contributions to L2 teaching development. Internationally, the perspective is afforded as the demands of current settings and necessities in the context of ELT, particularly the ones consider English as their second and foreign language usage. The diversion of ELT contexts in the world might trigger the imbalance use of teaching approaches, strategies, techniques and teaching model. Therefore, in bridging the gap of the imbalance, this paper suggests some worthy-applied approaches which might be taken as considerations. EFL practitioners, teachers, students, curriculum makers and school practitioners in the level of junior, senior high school and university can incorporate  the proposed lexically-based approaches in  their  teaching  and  conduct research  on  the  effectiveness  of  the  approaches and techniques  they  utilize. The effect of chunking, the learning of formulaic phrases, collocation instruction and conscious awareness of learning lexicon can add a different dimension to teaching that may result in better L2 proficiency.